Investigating Factors Affecting Listening Comprehension Skills in University Students - Ari Wibowo (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
This research study delved into the investigation of factors influencing listening comprehension skills in university students, focusing on six key factors: language proficiency, motivation, exposure to English, teaching methodology, cultural background, and technology integration. Language proficiency emerged as a foundational element, emphasizing the importance of a strong linguistic foundation encompassing vocabulary, grammar, and pronunciation for effective listening comprehension. Motivation was identified as a critical driver of students' engagement and persistence in developing their listening skills, highlighting the significance of intrinsic motivation in fostering active participation and enhancing comprehension levels. Exposure to authentic English language input, effective teaching methodologies, consideration of cultural backgrounds, and integration of technology were all found to play essential roles in shaping students' listening abilities, underscoring the multifaceted nature of factors influencing listening comprehension skills in university students. The findings of this study provide valuable insights for educators and stakeholders seeking to enhance students' listening abilities and promote successful language learning experiences. By recognizing the interconnectedness of language proficiency, motivation, exposure to English, teaching methodology, cultural background, and technology integration, educators can tailor instructional strategies to support students in developing proficient and confident listening skills. Collaborative efforts to address these factors in language education programs can lead to improved language learning outcomes, enriched cultural understanding, and enhanced communication skills for university students in academic and professional contexts.